REDEFINING REAL-EARNINGS MANAGEMENT: A CONSTRUCTIVE PERSPECTIVE OF A NON-OPPORTUNISTIC STRATEGY - Agus Sholikhan Yulianto (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This research investigates the hidden characteristics of real-earnings management (REM) as a competitive strategy, challenging the mainstream view of it as an opportunistic practice. This work employs a dynamic panel data two-step generalised method of moments (GMM). The sample comprises companies listed on the Indonesia Stock Exchange from 2009 to 2024. This paper presents crucial theoretical implications for real-earnings management as an efficient practice that challenges the mainstream view of opportunistic financial reporting. Firstly, the persistence of real-earnings management practice is evidence of a violation of the temporary or abnormal practice. Secondly, the interrelationships among the components form an internal supply chain. Third, the effects of real-earnings management on income sustainability are evident. Finally, the positive influence of the macroeconomic situation on the abnormal operating cash flow arrangement affirms the non-opportunistic nature of the practice. However, this paper also admits that ex post analysis is limited in its ability to characterise current REM. This paper provides a framework for future research to incorporate the still-unexplored potential determinants of each REM criterion, and the urgent need to complement these measurements with a regression residual model is clear.